PENYEMBELIHAN AYAM POTONG DIPASAR LOKAL INDONESIA MENURUT TINJAUAN HUKUM ISLAM MAZHAB SYAFI’I - M. Syam'un Rosyadi (al-Rasῑkh: Jurnal Hukum Islam, 2022)
This research discusses the slaughter of broiler chickens according to the rules that have been regulated by the Religious Shari'a, especially for adherents of the Imam Syafi'i school of thought. Moreover, Indonesia is a country where most of the people are guided by the Imam Syafi'i School. The research method used is descriptive qualitative research, namely data collected in the form of words, and pictures, not numbers. In the process of data analysis, the researcher used descriptive analysis by presenting data related to the Syafi'i school of thought regarding the slaughter of broiler chickens. In carrying out the slaughtering process, the person who slaughters must be a Muslim who is rational and has reached puberty or a mulatto and all the slaughtering processes are following the provisions and regulations of Shari'a law. And if it is not slaughtered following the regulations of the Shari'at law, then the animal is unlawful for consumption and is considered carrion because according to the Syafi'i School, animals that are haraam for slaughter are animals that are slaughtered by mentioning a name other than Allah's name or without mentioning it. The conclusion is that from the perspective of the Syafi'i School, it is permissible for a chicken to be slaughtered to be halal, just two jugular veins, namely hulqum and mari', are considered halal.